Blood Glucose Level Status in Low Birth Weight (LBW) Neonates (The Planet, 2023)
Introduction: LBW may occur when an infant is born tooprompt. According to severity, newborns can becategorized into three groups, such as very low birthweight baby (
Keywords: LBW; Hypoglycaemia; Neonates; Glycemic status